Welcome to Westonci.ca, the place where your questions are answered by a community of knowledgeable contributors. Get quick and reliable solutions to your questions from a community of experienced professionals on our platform. Our platform offers a seamless experience for finding reliable answers from a network of knowledgeable professionals.
Sagot :
To show that if [tex]\( x + y + z = 0 \)[/tex], then [tex]\( x^3 + y^3 + z^3 = 3xyz \)[/tex], let's proceed with the following steps:
### Step 1: Use the Identity for the Sum of Cubes
We start with a well-known algebraic identity for the sum of cubes:
[tex]\[ x^3 + y^3 + z^3 - 3xyz = (x + y + z)(x^2 + y^2 + z^2 - xy - yz - zx) \][/tex]
### Step 2: Substitute the Given Condition
Given that [tex]\( x + y + z = 0 \)[/tex], we substitute this into the identity:
[tex]\[ x^3 + y^3 + z^3 - 3xyz = (0)(x^2 + y^2 + z^2 - xy - yz - zx) \][/tex]
### Step 3: Simplify the Equation
Since any number multiplied by 0 is 0, the right-hand side of the equation becomes 0:
[tex]\[ x^3 + y^3 + z^3 - 3xyz = 0 \][/tex]
### Step 4: Rearrange to Show the Desired Result
Rearranging the equation, we get:
[tex]\[ x^3 + y^3 + z^3 = 3xyz \][/tex]
### Verification with Example Values
To confirm this identity, let's take specific values of [tex]\( x \)[/tex], [tex]\( y \)[/tex], and [tex]\( z \)[/tex] that satisfy [tex]\( x + y + z = 0 \)[/tex]. For instance, let [tex]\( x = 1 \)[/tex], [tex]\( y = -2 \)[/tex], and [tex]\( z = 1 \)[/tex]:
[tex]\[ x + y + z = 1 - 2 + 1 = 0 \][/tex]
This satisfies the given condition. Now, we calculate both sides of the equation:
1. Calculate the left side:
[tex]\[ x^3 + y^3 + z^3 = 1^3 + (-2)^3 + 1^3 = 1 - 8 + 1 = -6 \][/tex]
2. Calculate the right side:
[tex]\[ 3xyz = 3 \cdot 1 \cdot (-2) \cdot 1 = 3 \cdot (-2) = -6 \][/tex]
Both sides of the equation equal [tex]\(-6\)[/tex], confirming that the relation [tex]\( x^3 + y^3 + z^3 = 3xyz \)[/tex] holds true for these values.
Thus, we have shown that if [tex]\( x + y + z = 0 \)[/tex], then [tex]\( x^3 + y^3 + z^3 = 3xyz \)[/tex].
### Step 1: Use the Identity for the Sum of Cubes
We start with a well-known algebraic identity for the sum of cubes:
[tex]\[ x^3 + y^3 + z^3 - 3xyz = (x + y + z)(x^2 + y^2 + z^2 - xy - yz - zx) \][/tex]
### Step 2: Substitute the Given Condition
Given that [tex]\( x + y + z = 0 \)[/tex], we substitute this into the identity:
[tex]\[ x^3 + y^3 + z^3 - 3xyz = (0)(x^2 + y^2 + z^2 - xy - yz - zx) \][/tex]
### Step 3: Simplify the Equation
Since any number multiplied by 0 is 0, the right-hand side of the equation becomes 0:
[tex]\[ x^3 + y^3 + z^3 - 3xyz = 0 \][/tex]
### Step 4: Rearrange to Show the Desired Result
Rearranging the equation, we get:
[tex]\[ x^3 + y^3 + z^3 = 3xyz \][/tex]
### Verification with Example Values
To confirm this identity, let's take specific values of [tex]\( x \)[/tex], [tex]\( y \)[/tex], and [tex]\( z \)[/tex] that satisfy [tex]\( x + y + z = 0 \)[/tex]. For instance, let [tex]\( x = 1 \)[/tex], [tex]\( y = -2 \)[/tex], and [tex]\( z = 1 \)[/tex]:
[tex]\[ x + y + z = 1 - 2 + 1 = 0 \][/tex]
This satisfies the given condition. Now, we calculate both sides of the equation:
1. Calculate the left side:
[tex]\[ x^3 + y^3 + z^3 = 1^3 + (-2)^3 + 1^3 = 1 - 8 + 1 = -6 \][/tex]
2. Calculate the right side:
[tex]\[ 3xyz = 3 \cdot 1 \cdot (-2) \cdot 1 = 3 \cdot (-2) = -6 \][/tex]
Both sides of the equation equal [tex]\(-6\)[/tex], confirming that the relation [tex]\( x^3 + y^3 + z^3 = 3xyz \)[/tex] holds true for these values.
Thus, we have shown that if [tex]\( x + y + z = 0 \)[/tex], then [tex]\( x^3 + y^3 + z^3 = 3xyz \)[/tex].
Thank you for your visit. We're committed to providing you with the best information available. Return anytime for more. We appreciate your time. Please come back anytime for the latest information and answers to your questions. We're glad you chose Westonci.ca. Revisit us for updated answers from our knowledgeable team.